2016
DOI: 10.1080/17430437.2016.1173912
|View full text |Cite
|
Sign up to set email alerts
|

‘It brings the lads together’: a critical exploration of older men’s experiences of a weight management programme delivered through a Healthy Stadia project

Abstract: 'It brings the lads together': A critical exploration of older men's experiences of a weight management programme delivered through a Healthy Stadia project. AbstractOlder men whose weight is considered unhealthy may experience particular barriers that can restrict their adoption of health improvement interventions. Despite promising findings recommending the use of sports settings to facilitate health promotion with men, little evidence has addressed older men's health needs for, or experiences of, these sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
3
8
0
1
Order By: Relevance
“…How has this change occured within the context of Lorena's doctoral studies? (LOZANO-SUFRATEGUI, 2015 1 ; LOZANO-SUFRATEGUI et al, 2016a;2016b). Our exploration adds to existing accounts of the personal-professional transformations described by other researchers in the sport and physical activity area (CARLESS; DOUGLAS, 2010;CARLESS, 2015;SMITH, 2010).…”
Section: Introductionmentioning
confidence: 67%
“…How has this change occured within the context of Lorena's doctoral studies? (LOZANO-SUFRATEGUI, 2015 1 ; LOZANO-SUFRATEGUI et al, 2016a;2016b). Our exploration adds to existing accounts of the personal-professional transformations described by other researchers in the sport and physical activity area (CARLESS; DOUGLAS, 2010;CARLESS, 2015;SMITH, 2010).…”
Section: Introductionmentioning
confidence: 67%
“…For example, older women have described a sense of belonging that results from their involvement in structured exercise groups and sporting pursuits (Bidonde, Goodwin and Drinkwater 2009;Heuser 2005;Kluge et al 2012). Similar studies with older men have found that they emphasise the importance of the friendships with other men that arise from their participation in exercise and sporting groups (Grant 2012;Lozano-Sufrategui et al 2017;Minello and Nixon 2017).…”
Section: Subjective Experiences Of Physical Activity In Later Lifementioning
confidence: 91%
“…Additionally, older adults perceive exercise to be essential for the maintenance of their independence, health and wellbeing (Bidonde, Goodwin and Drinkwater 2009;Kluge et al 2012;Grant 2012;Lozano-Sufrategui et al 2017;Liechty et al 2014;Minello and Nixon 2017;Sims-Gould et al 2010). Some studies point to specific health and functional benefits that participants perceive result from their activities, such as improved balance, strength and flexibility (Bidonde, Goodwin and Drinkwater 2009).…”
Section: Subjective Experiences Of Physical Activity In Later Lifementioning
confidence: 99%
See 2 more Smart Citations